Apetamin Hepatotoxicity: Potential Consequences of Purchasing a Body Enhancement Drug Off the Internet. Issue 6 (23rd June 2020) - Garland, Victoria; Kumar, Anita; Theisen, Brian; Borum, Marie L.
ABSTRACT: We report Apetamin (cyproheptadine lysine and vitamin syrup), a non-US Food and Drug Administration-approved weight gain supplement, causing drug-induced autoimmune hepatitis. A 40-year-old previously healthy woman presented with fatigue, right-sided abdominal discomfort, and jaundice 6 weeks after starting Apetamin, which she learned from social media for figure augmentation. Labs were significant for elevated transaminases, positive smooth muscle antibody, and increased immunoglobulins. Biopsy indicated drug-induced autoimmune hepatitis. Symptoms improved with prednisone, azathioprine, and stopping Apetamin which contains cyproheptadine, a known hepatotoxin. The case reveals the influence of social media and its impact on health and the importance of a complete drug history.